Comparison of terpene components from flowers of Artemisia annua - Yang, Zhan-Nan; Zhu, Shi-Qiong; Yu, Zheng-Wen (Bangladesh Journal of Pharmacology, 2012)
Terpene constituents of essential oils obtained by steam distillation from Artemisia annua flowers at the pre-, full- and post-flowering stage was investigated by gas chromatography (GC) and gas chromatography-mass spectrometric detector (GC-MS). The aim was to evaluate change the biosynthesis pathway of terpenes at different flowering stages. The samples studied showed that main components of essential oils were monoterpenes hydrocarbons (48.1%) and oxygenated monoterpenes (41%) in the pre-flowering, oxygenated monoterpenes (35.6%) and sesquiterpenes hydrocarbons (5.0%) in the full-flowering, and oxygenated monoterpenes (29.6%), sesquiterpenes hydrocarbons (32.2%) and oxygenated sesquiterpenes (25.3%) in the post-flowering, respectively. The relative content of monoterpenes decreased from pre-flowering to post-flowering, while that of sesquiterpenes increased. The results indicated that the biosynthesis pathway of terpenes might be changed at different flowering at stages, while the change of content and composition of terpenes might be a self-adaptation of A. annua.